Perwujudan Profil Pelajar Pancasila Pada Pembelajaran Abad 21 Di SMA N 2 Medan - Ainun Palihah; Liesna Andriany (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Indonesian education is experiencing changes and developments through curriculum reform that is in line with current developments. Strengthening the character and values of Pancasila is emphasized in independent learning. Independent learning is a government breakthrough to develop the potential of students. In the independent curriculum there is a Pancasila student profile program to be implemented for students in 21st century learning. This research was conducted to find out how the Pancasila student profile is realized at SMA N 2 Medan. The results of this research show that SMA N 2 Medan has realized the Pancasila student profile in 21st century education. The realization of the Pancasila student profile consists of 6 dimensions, namely Faith, devotion to God Almighty, and noble character, global diversity, mutual cooperation, independence, thinking. critical and creative. The realization of the Pancasila student profile is side by side with 21st century education which leads to developing 4C skills